Improvement in cardio-metabolic health and immune signatures in old individuals using daily chores (Salat) as an intervention: A randomized crossover study in a little-studied population - Alam, Iftikhar; Ullah, Riaz; Jan, Attaullah; Sehar, Bismillah; Khalil, Atif Ali Khan; Naqeeb, Huma; Ali, Essam A.; Wahab, Qazi Muhammad Farooq; Safdar, Mahpara; Ali, Abid; Zaman, Muhammad Haidar; Zeb, Falak (Frontiers in Public Health, 2022)
Background Decline in cardio-metabolic health, immunity, and physical activity is associated with old age. Old people also find it difficult to engage in structured exercise programs. Therefore, there is a need to investigate common daily chores as an alternative for exercise that may also help in maintaining cardio-metabolic and immune health. Objective We aimed to investigate whether Salat, an obligatory Islamic prayer involving various physical movements and closely resembling yoga, enhances the benefits conferred by the current guidelines for physical activity. Methods A total of 30 overweight adults (mean (SD) age of 53.5 (8.7) years) participated in this study. For a 4-week duration, we compared the effects of Salat before/after meals (Pre-MS/Post-MS) on selected immunological and metabolic parameters in serum samples. We also compared the effects of both Pre-MS/Post-MS regimens in young and old subjects to observe any age-related effects. Results Most of the baseline metabolic parameters and the count of immune cells were normal. Post-MS resulted in a significant reduction in body weight and percent body fat (%BF). Overall, Post-MS resulted in a clear leukocytosis with a significant increase in granulocytes, monocytes, and lymphocytes. When analyzing the lymphocyte compartment, a clear numerical increase was noted for T, B, and NK cells. The number of CD8+ T cells showed a statistically significant increase. Similarly, Post-MS induced leukocytosis in both young and old individuals, while the increase in granulocytes, monocytes, and lymphocytes was statistically significant in old subjects only. Conclusion This study demonstrated that the Islamic obligatory and congressional Salat practice is capable of mimicking desirable pro-immune and pro-metabolic health effects. Clinical trial registration (UMIN000048901).